MEWUJUDKAN KEUANGAN YANG SEHAT MELALUI PENERAPAN PERENCANAAN DAN PENGELOLAAN KEUANGAN KELUARGA MANDIRI - Pipit Buana Sari; Handriyani Dwilita (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Family financial management is the basis of family financial health, starting with planning to consistent implementation as well as evaluation and feedback. This service activity is a series of service and research activities carried out by the implementing team in hamlet 20. Previously the team had conducted research related to community financial literacy, especially women or housewives in hamlet 20, Klambir Lima Kebun village. Then it was continued by carrying out community service activities in the form of a training workshop on making shredded vegetables made from vegetables, namely shredded banana and papaya fruit. From the series of three activities, it is hoped that women or housewives will have a direction towards financial independence. The team then carried out further service activities, namely socializing the use of the budget and managing family finances. This activity is in accordance with the objectives conveyed by the OJK for a prosperous family, the financial planning book reference from the OJK is used in this activity. The result of this activity is that housewives still find it difficult to start implementing the science that the team conveys, because it is a smelly thing and really needs desire and consistency. However, the housewives in Dusun 20 welcomed our presentation when we explained the advantages of having a good financial plan to achieve a more prosperous family. The problem of family welfare lies not only in the amount of sufficient income but also in healthy financial management